Industrial Biorefineries and White Biotechnology - Pandey, Ashok; Höfer, Rainer; Larroche, Christian; Taherzadeh, Mohammad; Nampoothiri, K. Madhavan (Elsevier Ltd., 2015)
Industrial Biorefineries and White Biotechnology provides a comprehensive look at the increasing focus on developing the processes and technologies needed for the conversion of biomass to liquid and gaseous fuels and chemicals, in particular, the development of low-cost technologies. During the last 3-4 years, there have been scientific and technological developments in the area; this book represents the most updated information and technological perspective on the topic.